Biculturalism and Self-Esteem: Differential Associations Based on Cultural Domain - Garcia Peraza, Paulette D.; Nguyen, Angela-MinhTu D.; Corona, Joshua; Amini, Sadie S. (Hispanic journal of behavioral sciences, 2021)
Acculturation is multidimensional in that it encompasses both heritage and dominant cultural orientations, and it can take place across multiple domains; therefore, biculturalism, an acculturation strategy involving strong orientations to both heritage and dominant cultures, can also occur for the domains of behaviors and practices, values and beliefs, and cultural identity. The current study is the first to compare the relations between biculturalism and self-esteem across these three cultural domains. Mexican American undergraduate students (N = 219; Mage = 18.82 years, SD = 1.09), who were primarily women (72.15%) and born in the US (81.74%), responded to an in-person survey. We found that biculturalism is differentially associated with personal and collective self-esteem depending on the domain, with stronger associations for bicultural behaviors and weaker associations for bicultural values. Our findings highlight the importance of recognizing the multidimensionality of biculturalism in theory, research, and practice.